Frequency based capacitive biosensor - El-Sehrawy, Yehia (AUC Knowledge Fountain, 2020)
Unlike traditional medical equipment that tend to be bulky and expensive, biosensors are portable, versatile, and inexpensive for mass production. Biosensors allow for early detection of disease due to their wide reach which increases the patients’ chances of recovery. The literature presents several biosensor techniques based on DNA hybridization, contact imagers, and capacitance transduction. This thesis presents a ring oscillator based biosensor that uses capacitance to frequency transduction for the detection of viral and cancer diseases. The design features a differential measurement to eliminate the effect of parasitic capacitances on the measurement. In order to mitigate the typical errors of process variations associated with differential designs, the design features an automatic calibration system using a feedback loop from the output to synchronize the sensing and reference oscillators. The design is implemented on Virtuoso Analog Design Environment – Cadence using 130 nm CMOS technology. The design was tested for its ability to synchronize and automatically calibrate its reference ring oscillator to the frequency of the sensing ring oscillator. The design was also tested for its ability to detect and measure frequency changes resulting from introduced capacitive changes to the sensing oscillator in the atto and femto farad ranges. Results from the simulations show that the sensor features ±2.3% process variation compensation, minimum input capacitance of 5 aF, 1 attofarad resolution, and 106 kHz/aF sensitivity. The design’s performance proves its ability to be used for a wide array of sensing applications.